2013
DOI: 10.1371/journal.pone.0069227
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Concentration Measurement during Hemodialysis through Ion-Exchange Resin and Conductivity Measure Approach: In Vitro Experiments

Abstract: Sodium measurement during hemodialysis treatment is important to preserve the patient from clinical events related to hypo- or hyper-natremia Usually, sodium measurement is performed through laboratory equipment which is typically expensive, and requires manual intervention. We propose a new method, based on conductivity measurement after treatment of dialysate solution through ion-exchange resin. To test this method, we performed in vitro experiments. We prepared 40 ml sodium chloride (NaCl) samples at 280, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Correlation accounts for the presence of offset and gain between the 2 compared variables, but the high estimated R 2 value could only be obtained in the case of very similar time dynamics. Values of the regression coefficients are similar to values reported in the literature for the relationship between sodium concentration and conductivity in dialysate: for example, Tura et al (35) reported σ Dial = 0.08•Na Dial + 2.87. The value of the obtained regression slope, 0.092 (mS/cm)/mM, and the presence of a 1.068 mS/cm offset can be explained by the influence of ions other than sodium on total conductivity, as already mentioned in the Methods section.…”
Section: Discussionsupporting
confidence: 82%
“…Correlation accounts for the presence of offset and gain between the 2 compared variables, but the high estimated R 2 value could only be obtained in the case of very similar time dynamics. Values of the regression coefficients are similar to values reported in the literature for the relationship between sodium concentration and conductivity in dialysate: for example, Tura et al (35) reported σ Dial = 0.08•Na Dial + 2.87. The value of the obtained regression slope, 0.092 (mS/cm)/mM, and the presence of a 1.068 mS/cm offset can be explained by the influence of ions other than sodium on total conductivity, as already mentioned in the Methods section.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, this measurement method has potential in biotechnology and medical technology for the contactless determination of biomass within single-use bioreactors [1,18] or for obtaining tissue information [19][20][21][22][23]. In addition, the differential transformer approach is investigated with respect to continuous in-line monitoring of the sodium concentration in human blood, by measuring the blood plasma conductivity, mainly influenced by the sodium concentration [24][25][26][27]. Continuous monitoring of plasma sodium concentration is particularly important in continuous renal replacement therapy, especially in patients with severe dysnatremia, since both a large deviation from the physiological plasma sodium level [26,[28][29][30] and a rapid change in the concentration can lead to dangerous complications such as central pontine myelinolysis [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Because the conductivities of single ions cannot be measured independently of their counter ions, the conductivities of KCl and NaCl solutions have to be used instead. σ K / σ Na depends only slightly on the actual ion strength and can be deduced from in vitro measurements: Tura et al found conductivities of 12.93 and 15.92 mS/cm, for a 140 mmol/L sodium chloride or potassium chloride solution respectively. This leads to σ K / σ Na = 1.231.…”
Section: Discussionmentioning
confidence: 99%